2021
DOI: 10.3390/ijerph18157879
|View full text |Cite
|
Sign up to set email alerts
|

Deep Venous Thrombosis and Risk of Consequent Sepsis Event: A Retrospective Nationwide Population-Based Cohort Study

Abstract: Deep vein thrombosis causes several acute and chronic vessel complications and puts patients at risk of subsequent sepsis development. This unique study aimed to estimate the risk of sepsis development in DVT patients compared with non-DVT patients. This population-based cohort study used records of a longitudinal health insurance database containing two million patients defined in Taiwan’s National Health Insurance Research Database (NHIRD). Our study included patients aged over 20 years with a new diagnosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 45 publications
(47 reference statements)
0
4
0
Order By: Relevance
“…Sepsis has been shown to be an independent risk factor for VTD (OR 1.74; 95%CI, 1.59-1.90). Risk factors associated with sepsis include age, diabetes, chronic kidney disease, chronic obstructive pulmonary disease, stroke, malignancy and antibiotic use (27), most of which are risk factors for thrombosis. Among septic patients, those requiring mechanical ventilation (28) had a higher risk of thromboprophylaxis failure, suggesting that the greater the severity of the infectious process, the greater the risk of thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…Sepsis has been shown to be an independent risk factor for VTD (OR 1.74; 95%CI, 1.59-1.90). Risk factors associated with sepsis include age, diabetes, chronic kidney disease, chronic obstructive pulmonary disease, stroke, malignancy and antibiotic use (27), most of which are risk factors for thrombosis. Among septic patients, those requiring mechanical ventilation (28) had a higher risk of thromboprophylaxis failure, suggesting that the greater the severity of the infectious process, the greater the risk of thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…POCUS seems to be of great utility for the identification of deep vein thrombosis-associated complications, which could potentially serve as the initial nidus of sepsis. The major complication is septic thrombophlebitis, whichis commonly seen in intravenous drug users or patients with indwelling central venous catheters and less frequently in the rather rare clinical entity called Lemierre syndrome [ 52 , 53 ]. In septic thrombophlebitis, US shows a non-compressible vein with an anechoic or echogenic thrombus in its lumen, vessel wall thickening and loss of colour Doppler flow.…”
Section: Pocus As a Tool For Diagnosismentioning
confidence: 99%
“…In addition, DVT may exacerbate the pathophysiologic disorders of sepsis. A large cohort study found that beyond inducing various acute and chronic vascular complications, DVT also served as a risk factor for sepsis [5].…”
Section: Introductionmentioning
confidence: 99%